Pondok Pesantren Merupakan Sebuah Sistem Dalam Pendidikan Islam - Abdul Hadi (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2022)
As the basis of Islamic education, Islamic boarding schools can indeed be said to be strategic places in giving birth to scholars, clerics, and even big figures who have a high understanding of the religion of Islam. The research method used is library research or library research. Meanwhile, what is meant by literature review research is a study carried out to solve a problem which basically relies on critical and in-depth research on relevant library materials. Library materials are used to explore new ideas as the basis for carrying out deductions from existing knowledge. As an Islamic educational institution, pesantren from a historical cultural point of view can be said to be a "training center" which automatically becomes the "cultural central" of Islam developed by the community, at least by the Islamic community itself which de facto cannot be ignored by the government. Islamic boarding schools today, in the implementation of the education and teaching system at Islamic boarding schools, can be classified into three forms, namely: a) Islamic boarding schools are Islamic education and teaching institutions, which are generally given in a non-classical way and the students usually live in Islamic boarding schools. or dormitory in the boarding school. b) Pesantren is an Islamic education and teaching institution, whose students are not provided with accommodation in the pesantren complex, but live scattered around the village around the pesantren. Where the ways and methods of Islamic education and teaching are given with the weton system, where the students come in flocks at certain times. c) Islamic boarding schools today are combined institutions between the boarding school system and Islamic boarding schools that provide Islamic religious education and teaching with the bandungan, sorogan, or wetonan systems, for which students are provided with boarding houses commonly called Modern Islamic Boarding Schools that meet the criteria for non-formal education as well as organizing formal education, both madrasas and public schools at various levels